2004
DOI: 10.1111/j.1479-828x.2004.00243.x
|View full text |Cite
|
Sign up to set email alerts
|

Single or multiple embryo transfer following in vitro fertilisation for improved neonatal outcome: A systematic review of the literature

Abstract: Information on neonatal and maternal outcomes following transfer of different numbers of embryos is limited. Transfer of one embryo does not alter the likelihood of a singleton pregnancy or birth when compared to transfer of two or more embryos. Transfer of one or two embryos decreases the risk of a multiple pregnancy, preterm birth and low birthweight. Further large, well-designed randomised trials are required to provide maternal and neonatal outcomes of relevance to a couple undergoing IVF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 46 publications
0
2
0
2
Order By: Relevance
“…The rationale for favouring DET over SET, until recently, has been that the transfer of two or more embryos results in a higher clinical pregnancy rate than the transfer of only one embryo, especially in younger women 15 . However, a higher clinical pregnancy rate does not mean better perinatal outcomes for the baby.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for favouring DET over SET, until recently, has been that the transfer of two or more embryos results in a higher clinical pregnancy rate than the transfer of only one embryo, especially in younger women 15 . However, a higher clinical pregnancy rate does not mean better perinatal outcomes for the baby.…”
Section: Discussionmentioning
confidence: 99%
“…They compared the outcome of double embryo transfer with that of three-or-more embryo transfer. They found that the transfer of two embryos was associated with a lower incidence of live birth at term, clinical pregnancy, multiple pregnancy and multiple birth, twin birth, triplet or higher order pregnancy, and triplet or higher order births (Dare et al ., 2004). This difference might be explained by the improvement in technology during the last ten years.…”
Section: Discussionmentioning
confidence: 99%
“…Outro grande desafio na reprodução assistida é a tentativa de se minimizar a incidência de gestação múltipla secun-dária aos tratamentos. Assim, nas técnicas de fertilização in vitro, têm-se tentado cada vez mais a transferência de um embrião único (Dare et al, 2004). E a forma para se conseguir isso é a transferência de embriões no estágio de blastocisto, pois assim, há uma melhor seleção embrionária.…”
Section: Introductionunclassified